2001
DOI: 10.2355/isijinternational.41.1236
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Iron and Steel Making Processes. Effect of Magnetic Field Conditions on the Electromagnetic Braking Efficiency.

Abstract: Effect of different types of in-mold electromagnetic brake (EMBr) technique, which forms a local magnetic field and a level magnetic field in the width direction of a mold, on the fluid flow phenomena in the strand pool was examined. A mercury model experiment revealed that the level magnetic field developed a pluglike flow in the strand pool, of which flow could not be obtained by the local magnetic field. Surface velocity near the meniscus could be stably controlled with the level magnetic field, while in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 2 publications
2
34
0
Order By: Relevance
“…[8] This set of coupled MHD equations (Eqs. [1]- [5]) is solved by the finite volume method and implemented on a graphics processing unit (GPU) for fast computation in the in-house code CUFLOW. The numerical details of solving these equations with CUFLOW have been discussed in previous studies, [16][17][18][19] and hence, are only briefly described in Section II-F.…”
Section: A Governing Equations For Les Of Magnetohydrodynamic (Mhd) mentioning
confidence: 99%
See 1 more Smart Citation
“…[8] This set of coupled MHD equations (Eqs. [1]- [5]) is solved by the finite volume method and implemented on a graphics processing unit (GPU) for fast computation in the in-house code CUFLOW. The numerical details of solving these equations with CUFLOW have been discussed in previous studies, [16][17][18][19] and hence, are only briefly described in Section II-F.…”
Section: A Governing Equations For Les Of Magnetohydrodynamic (Mhd) mentioning
confidence: 99%
“…Statically-applied electromagnetic-field (EMF) configurations include local [circular fields on each side of the Submerged Entry Nozzle (SEN)], [1][2][3][4][5] single-ruler (a rectangular field across the entire mold width), [5,6] and double-ruler [6][7][8][9] (two rulershaped fields, with one positioned across the mold near the meniscus and the other one aligned through or below the nozzle ports). When the EMF coil currents are adjusted to produce equal peak field strengths, this double-ruler configuration is commercially known as ''Flow-Control-Mold'' or ''FC-Mold'' ElectroMagnetic Braking or ''EMBr.''…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] For example, Cukierski and Thomas reported that local EMBr usually decreases the surface velocity, depending on the submergence depth of the Submerged Entry Nozzle (SEN). 8) Wang and Zhang investigated the effects of local EMBr on the fluid flow, heat transfer, and transport of argon bubbles and inclusions in the mold.…”
Section: Introductionmentioning
confidence: 99%
“…Of these efforts, utilization of direct current (DC) magnetic fields started with a localized electromagnetic brake 2) aimed at reducing the velocity of the outlet stream from the submerged entry nozzle (SEN) and is now changing to a full-width electromagnetic brake 3,4) as a nextgeneration electromagnetic brake with superior control capability.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The flow of molten steel in the mold is controlled by changing the downward flow velocity and penetration depth in the mold and the flow velocity and temperature of molten steel in the meniscus through application of the LMF electromagnetic brake. 5) Consequently, the length of intermixed compositions formed during sequence casting of dissimilar grades of steels is shortened, 6) and the number of nonmetallic inclusions in the cast slabs is reduced.…”
Section: Introductionmentioning
confidence: 99%